IMPLEMENTATION OF MOBILE GOVERNMENT BASED INFORMATION TECHNOLOGY AS A SOLUTION FOR THE PROGRESS OF PEKON BLITAREJO - Nungsiyati, Nungsiyati; Abidin, Ali Zainal; Muslihudin, Muhamad (IJISCS (International Journal of Information System and Computer Science), 2024)
Technology is a result of the thoughts that exist in humans in developing a method in a certain system so that it can be useful, then to use it to solve problems that exist in human life itself. While the definition of the information itself is a news in which it contains a certain purpose or element, so that humans can have a knowledge and an experience that basically always wants to be shared with others. So, the purpose of the statement above can be concluded that information technology is a procedure or system used by humans to convey messages or information. The mobile application is an easy means of moving from one place to another, Government technology is a form of electronic technology that is used in an effort to implement existing government activities internally and externally with the aim of achieving efficiency, effectiveness and speed in any case. Smart City is a modern city or smart city. Meanwhile, a smart urban system for example can provide high economic value for money in the context of better traffic management.